2014
DOI: 10.1556/aling.61.2014.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Emotional activation measured using the emotional Stroop task in early Hungarian-Serbian bilinguals from Serbia

Abstract: The primary goal of this research was to examine the processing of emotionally valenced and neutral words in the context of bilingualism. The objective was to find out, using an experimental measure of automatic emotional activation, if there were differences in response time in the first and the second language, Hungarian and Serbian respectively. The sample consisted of early Hungarian-Serbian bilinguals, assimilated into the Serbian majority culture.The emotional Stroop task is an experimental paradigm, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
1
16
1
1
Order By: Relevance
“…However, previous studies showing dampened affective sensitivity in L2 stand in contrast to results from cognitive studies using behavioral paradigms such as the emotional Stroop task (Sutton et al., 2007; Eilola et al., 2007; Grabovac and Pléh, 2014; but see Winskel, 2013), the affective priming task (Degner et al., 2012) or the emotional word recall and recognition task (Ferré et al., 2010; Ferré et al., 2013; but see Baumeister et al., 2017). Indeed, the latter studies have reported little or no difference in the automaticity of emotional word processing across L1 and L2 (for most recent reviews, see Caldwell-Harris, 2015; Jończyk, 2016a).…”
Section: Introductionmentioning
confidence: 68%
“…However, previous studies showing dampened affective sensitivity in L2 stand in contrast to results from cognitive studies using behavioral paradigms such as the emotional Stroop task (Sutton et al., 2007; Eilola et al., 2007; Grabovac and Pléh, 2014; but see Winskel, 2013), the affective priming task (Degner et al., 2012) or the emotional word recall and recognition task (Ferré et al., 2010; Ferré et al., 2013; but see Baumeister et al., 2017). Indeed, the latter studies have reported little or no difference in the automaticity of emotional word processing across L1 and L2 (for most recent reviews, see Caldwell-Harris, 2015; Jończyk, 2016a).…”
Section: Introductionmentioning
confidence: 68%
“…Employing the emotional Stroop paradigm, Eilola et al (2007) and Sutton et al (2007) examined the automatic access of emotional information in early L2-dominant Spanish-English bilinguals and late Finish-English bilinguals, and they found the same amount of interference in the bilinguals’ two languages with negatively valenced emotion words and neutral control words. Grabovac and Pléh (2014) compared the early Hungarian-Serbian bilinguals’ activation of emotionally charged words and neutral words, and similar pattern of interference was observed in their two languages. Contradictory research findings have also been reported in the emotional Stroop task in bilinguals.…”
Section: Introductionmentioning
confidence: 68%
“…Prior analyses of Stroop and Stroop-like tasks on the emotionality of L1 and L2 emotion words rely heavily on behavioral evidence either pointing to the attenuated emotionality in L2 as compared to L1 (e.g., Eilola and Havelka, 2011; Winskel, 2013) or the same amount of interference in the activation of emotional information in the bilinguals’ two languages (Eilola et al, 2007; Grabovac and Pléh, 2014). However, studies intending to directly contrast ERPs for the bilinguals’ emotion word processing in their two languages are scant.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Kazanas and Altarriba (2016) showed faster responses to emotionladen words but only in English among Spanish-English bilinguals living in the United States. Not all studies have shown greater emotional responses to the majority language (e.g., Grabovac and Pléh, 2014). The present study was carried out in an English-majority-language part of Canada.…”
Section: Introductionmentioning
confidence: 92%
“…The emotional links established in childhood may not explain all the results with bilinguals' emotional responses. Not all studies have found an L1 advantage in emotional processing (Ayçiçegi-Dinn and Caldwell-Harris, 2009;Ferré et al, 2010;Grabovac and Pléh, 2014;Kazanas and Altarriba, 2016;Ponari et al, 2015;Sutton et al, 2007). One possible reason for the lack of consistent L1 advantage across studies is that context of acquisition may play an important role.…”
Section: Introductionmentioning
confidence: 99%